QUALITY OF LIFE FOR PATIENTS WITH TRIGEMINAL NEURALGIA BEFORE AND AFTER MICROVASCULAR DECOMPRESSION - Mirzaev, A.U.; Yuldashev, O.T. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
To study the quality of life of patients with trigeminal neuralgia after surgical treatment with the method of microvascular root decompression before and after surgery. Material and methods: The results of observations of 409 patients with trigeminal neuralgia before and after microvascular decompression of the trigeminal root, which were treated in 2012- 2018, were analyzed. All patients were examined according to the standard scheme. Results: Microvascular decompression of the trigeminal root was an effective method of surgical treatment in patients with trigeminal neuralgia of all groups. The quality of life reflects the impact of the disease and treatment on the well-being of the patient and characterizes his physical, emotional and social well-being, which change under the influence of the disease or its treatment. Conclusions: The use of questionnaires in patients with trigeminal neuralgia is an important criterion for evaluating the effectiveness of treatment.